Oocyte aging in a marine protostome worm: The roles of maturation‐promoting factor and extracellular signal regulated kinase form of mitogen‐activated protein kinase - Stricker, Stephen A.; Beckstrom, Bradley; Mendoza, Cristina; Stanislawski, Emma; Wodajo, Tewodros (Development, growth & differentiation, 2016)
The roles of maturation‐promoting factor (MPF) and an extracellular signal regulated kinase form of mitogen‐activated protein kinase (ERK MAPK) are analyzed during oocyte aging in the marine protostome worm Cerebratulus. About a day after removal from the ovary, unfertilized metaphase‐I‐arrested oocytes of Cerebratulus begin to flatten and swell before eventually lysing, thereby exhibiting characteristics of a necroptotic mode of regulated cell death. Based on immunoblots probed with phospho‐specific antibodies, MPF and ERK are initially active in freshly mature specimens. However, as oocytes age, both kinase activities decline, with ERK deactivation occurring well before MPF downregulation. Experiments using pharmacological modulators indicate that oocyte degradation is promoted by the maturation‐initiated activation of ERK as well as by the deactivation of MPF that occurs in extensively aged specimens. The potential significance of these findings is discussed relative to previously published results for apoptotic eggs and oocytes of echinoderm and vertebrate deuterostomes. To supplement studies of other oocytes, morphological patterns of extraovarian aging are described for metaphase‐I‐arrested oocytes produced by Cerebratulus, an externally fertilizing marine worm of the phylum Nemertea. In addition, pharmacological modulators are combined with immunoblotting assays to provide data for this protostome that can be compared with previous reports for echinoderm and vertebrate deuterostomes.